Revitalize Your Skin: A Comprehensive Review of Chemical peel - Patole, Shravani Prakash; Naikawadi, Nishigandha D.; Redasani, Dr. V.K. (Asian Journal of Pharmaceutical Research and Development, 2024)
Recent years have seen tremendous progress in the realm of cosmetic science, with chemical peels becoming a well-liked method for improving and rejuvenating skin. In the field of cosmetic science, a chemical peel entails applying chemical solutions to the skin in order to induce controlled skin peeling and exfoliation. The goals of this operation are to minimize small lines, improve the texture of the skin, and treat conditions like hyperpigmentation or acne. The degree of skin penetration and the ensuing consequences are determined by the peel’s depth. Chemical peels can be classified as superficial, medium, or deep, with each type providing unique advantages and things to think about. All things considered, they are essential for skin rejuvenation since they encourage the removal of damaged skin layers, exposing skin that is smoother and looks younger.